Health Promoting Phytochemicals Their Concentration and Antioxidant Activity of Wild Edible Fruits of Uttarakhand, India - Saklani, Sarla; Badhani, Amit; Prakash Mishra, Abhay; Chandra, Subhash (Asian Journal of Chemistry, 2012)
Fragaria indica, Prunus armeniaca, Pyracantha crenulata and Rubus ellipticus belong family-Rosaceae, have great importance due to the presence of bioactive chemical constituents. By solvent extraction method fruit extracts were analyzed using HPLC and antioxidant activity was done by using DPPH, ABTS and FRAP method. Among all fruits, Fragaria indica had highest value of ascorbic acid (5.93 ± 0.40 mg /100g fw) and the same fruit species had lowest anthocyanin content (0.09 ± 0.02 mg/100 g fw) in the middle of all fruits. Total antioxidant activity, measured by the DPPH method ranged from 19.18 ± 0.14 to 29.22 ± 0.08 mM AAE/ 100 g fw, measured by the ABTS method, ranged from 0.47 ± 0.01 mM AAE/100 g to 4.41 ± 0.03 mM AAE/100 g fw and FRAP value was found within the range 0.09 ± 0.01-3.23 ± 0.03 mM AAE/100g fw.